1993
DOI: 10.1080/00087114.1993.10797262
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric inversion and X chromosome polymorphism inRhipidomyssp. (Cricetidae, Rodentia) from Brazil

Abstract: SUMMARY -Specimens of Rhipidomys collected in the states of Goias and SaoPaulo were analyzed cytogenetically and three karyotypes were identified, all with 2n = 44. A heterozygous pericentric inversion in pair 10, responsible for the variation in the fundamental number (FN = 48 and 49), was detected. Three types of X chromosomes were found: a large acrocentric (Xa) and two large submetacentrics (Xb and Xb + ). Comparisons between the G-banding patterns of our sample and of animals collected in other states all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
2
16
1
1
Order By: Relevance
“…Thus, the differences in the number of the Ag-NORs per cell may reflect differences in the number of active ribosomal sites in the last interphase (THIRIOT-QUIÉVREUX & INSUA 1992, GALETTI et al 1995. This polymorphism in the number of active NOR sites per cell seems to be common in rodents and has been reported for other species (YONENAGA-YASSUDA et al 1992, SVARTMAN & ALMEIDA 1993, LIMA et al 2003, SOUZA et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the differences in the number of the Ag-NORs per cell may reflect differences in the number of active ribosomal sites in the last interphase (THIRIOT-QUIÉVREUX & INSUA 1992, GALETTI et al 1995. This polymorphism in the number of active NOR sites per cell seems to be common in rodents and has been reported for other species (YONENAGA-YASSUDA et al 1992, SVARTMAN & ALMEIDA 1993, LIMA et al 2003, SOUZA et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Nesokia indica it has been suggested that selective pressure favoring specimens with large blocks of constitutive heterochromatin in the X and Y chromosomes promoted reduction of fertility [Thelma et al, 1988;Juyal et al, 1989]. However, this is a debatable issue since polymorphism in the amount of constitutive heterochromatin in sex chromosomes is quite common in some rodent groups, including the sigmodontines Euryoryzomys, Oligoryzomys, Nectomys , and Rhipidomys , and the echimyids Trichomys and Clyomys Yonenaga-Yassuda, 1982, 1984;Leal-Mesquita et al, 1993;Svartman and Almeida, 1993;Yonenaga-Yassuda, 1997, 1998]. Therefore, the biological meaning of the variation of heterochromatin amounts between both species of Deltamys remains unclear for the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies performed in one species from Colombia (Gardner and Patton 1976), 2 from Venezuela (Aguilera et al 1994), and in 8 from Brazil (Zanchin et al 1992, Svartman and Almeida 1993, Silva and Yonenaga-Yassuda 1999, showed that, with the exception of one, all species of this genus have the same diploid number (44), apparently differing among themselves only by the number of biarmed elements they carry (autosomal arms numbers ranging from 48 to 74).…”
Section: Introductionmentioning
confidence: 99%
“…Circles: Rhipidomys nitela; squares: R. leucodactylus cytotypes; lozenges: R. mastacalis cytotypes. Numbers 1, 5, 9 and 11 -this paper; 2, 7 and 8 -Silva and Yonenaga-Yassuda (1999); 3 -Aguilera et al (1994); 4 -Gardner and Patton (1976); 6, 13-16 -Zanchin et al (1992); 10 and 12 -Svartman and Almeida (1993).…”
mentioning
confidence: 99%